The Use of Instagram Social Media @Buna.Indonesia in Promoting Buna Indonesia Coffee Shop to Customers - Saputra, Ikhsan (Golden Ratio of Data in Summary, 2024)
This study aims to determine the use of Instagram social media @buna.indonesia in promoting Buna Indonesia coffee shop to customers and to find out the obstacles faced by the use of Instagram social media @buna.indonesia in promoting Buna Indonesia coffee shop to customers. In obtaining the data needed for this study, researchers used qualitative methods, descriptive research type with a case study approach. The results of this study indicate that AISAS Theory in particular plays an important role in explaining how @buna.indonesia succeeds in attracting audience attention through interesting and interactive visual content. Researchers also found obstacles faced in using Instagram social media, namely unexpected Instagram algorithm changes that often reduce the reach and visibility of content, limited features, limited resources, including time, energy, and budget. Increased competition in the coffee industry also adds to the complexity of the challenges faced.